STEAM Education : Intersections and Thresholds - Cooper, Yichien,; Lai, Alice, (Educational Research E-Books Online, Collection 2025., 2025)
Integrating science, technology, engineering, arts, and mathematics into a holistic and robust STEAM education is a promising educational movement worldwide. STEAM Education: Intersections and Thresholds features four themes-pedagogical frameworks, community-based learning, STEM‒STEAM transformation, and teacher education practices-examined by researchers, educators, policymakers, and community organizers from around the world. Readers will find unique and innovative curricular ideas, instructional strategies, STEAM gadgets, examples of real classroom activities, and projects for students from elementary to graduate school to enrich STEAM education. This collection of best practices is a must-have to build diverse, integrative, and engaging STEAM experiences in the 21st Century. Contributors are: Lori Czop Assaf, Paul Boey, Hsin-Yi Chao, Yichien Cooper, Yeliz Erdoğan, Suzan Duygu Bedir Erişti, Maria Evagorou, Jonah B. Firestone, Snow Yunxue Fu, David Glassmeyer, Luke Hampton, Kevin Hsieh, Sean Justice, Chia-Hung Kao, Alice Lai, Christine Liao, Don McMahon, Isao Ohashi, Vedat Özsoy, Eliza Pitri, Shyh-Shiun Shyu, Debrah C. Sickler-Voigt, Agni Stylianou-Georgiou, Michael White, So Lan Wong, and Yui-Chih Wu.